Adhesion enhancement of sol–gel coating on polycarbonate by heated impregnation treatment - Wu, Linda Y. L. (2013)
The main limitation in using coated plastics for optical components, electronic applications and display systems is the softness of the substrate surfaces, which is responsible for the low impact and abrasion resistance and weak adhesion between the coating and the substrate. In this paper, we report a new strategy for surface pre-treatment of plastics using heated vacuum equipment and sol–gel materials to provide both chemical bonds and penetrated hard layer into the plastic surface to increase the overall performance of the coated plastic components. The heated vacuum treatment process involves: (1) surface cleaning and pore opening by heating and vacuum conditions, (2) impregnation of hydrolyzed hybrid precursor into polymer substrate under pressure and elevated temperature, (3) aminolysis of diffused precursor with surface to form chemical bonds and hardened surface layer, (4) formation of chemical bonds at treated surface with sol–gel hard coating. An impregnation depth of 1.5 µm was detected. Water contact angle dropped to below 40° and roughness increased after treatment. These provided better adhesion by increased wettability and contact area. Much increased nanoindentation hardness and Young's modulus after impregnation provided a gradient in mechanical properties between soft substrate and hard sol–gel coating. The hardened substrate delays the plastic deformation in substrate during pencil scratch test, thereby preventing early gouge failure. Both the better adhesion and the delayed gouge failure contributed to the increased scratch resistance from 6B to 8H after sol–gel coating.